Entre afetos, cognições e cuidados: ambiências bioecológicas na educação infantil (0-3 anos) - Moura, Lílian dos Santos Pomina de (2023)
This Dissertation project is part of the Research Line “Teaching, knowledge and professional development”, of the Graduate Program in Education at the Federal University of Santa Maria (UFSM) - Master's Degree in Education. It introduces as the main question of the research: How do kindergarten teachers interact with babies and very young children when they play a leading role in exploratory bioecological ambiences in the first three years of Early Childhood Education? The Systematic Literature Review (SLR) raised the Current State of the Question, focusing on journals and academic works (dissertations and theses) on Early Childhood Education in the Education Area, covering the Bioecological Theory of Human Development and/or the educational approach of Reggio Emilia. The theoretical matrix was based on the Bioecology of Human Development, proposed by Urie Bronfenbrenner, sharpening the teacher's gaze towards children's attributes, that is, the characteristics of dispositions, resources and demands that favour/hinder interactions and inter-environmental knowledge. Also, in the concept of playful protagonism of the child comes from the educational approach of Reggio Emilia, advocated by the pedagogue Loris Malaguzzi. These references found resonance in the National Common Curricular Base – BNCC, its fundamental principles, experiential fields and learning objectives in Brazilian Early Childhood Education. The Bioecological Model or PPCT Model (Process-PersonContext-Time), proposed by Bronfenbrenner and Morris (1998), allowed understanding the development of children and their learning processes in kindergarten and nursery. The academic writing was elaborated as an autobiographical memorial of the kindergarten teacher and author, in the perspective of Magda Soares, establishing comprehensive connections with the PPCT Model. Although learning in/from teaching has been very significant, we have not forgotten to point out the COVID 19 Pandemic as an important challenge in recent years and as markers of this generation.